Identification and characterisation of a lithium mimetic: enzymatic, cellular and animal investigations - Singh, N (2012)
It has been six decades since the discovery of lithium for the treatment of bipolar disorder. There is, as yet, no conclusive evidence as to how lithium produces this therapeutic effect, since it is known to interact with multiple cellular targets. One of the most credible targets is the enzyme, inositol monophosphatase (IMPase), which plays a crucial role in cell signalling. My aim was to find a novel IMPase inhibitor and evaluate it as a possible lithium-like mood stabiliser by using enzyme, cell and whole animal experiments. To achieve this, I created recombinant human and mouse IMPase enzymes and then used these for screening and crystallisation. I used two different approaches for the small-molecule screening: substrate-based virtual screening and drug repositioning using a library of compounds with clinically proven safety. I identified ebselen as a novel IMPase inhibitor suitable for drug repositioning. I determined that ebselen inhibited IMPase noncompetitively, likely through a covalent modification on a cysteine. In cell cultures, ebselen was found to inhibit not just IMPase but other steps that resulted in accumulation of higher inositol phosphates. When injected intraperitoneally into mice, ebselen crossed the blood- brain barrier and exhibited inhibition of IMPase ex vivo. Moreover, in mice, ebselen simulates some, but not all, of the behavioural effects of lithium. I have determined that ebselen inhibits IMPase and acts as a partial lithium mimetic. Given that ebselen is safe in man, it warrants clinical testing for the treatment of bipolar disorder.